Pengaruh CR, QR, DER dan TATO terhadap ROA PT Pyridam Farma Tbk Periode 2012-2021 - Fany Oktaviani; Andre Suryaningprang; Erna Herlinawati; Yoyo Sudaryo (Journal Of Business, Finance, and Economics (JBFE), 2022)
The purpose of this research is to find out how the effect of “Debt to Equity Ratio (DER)”, “Total Asset Turnover (TATO)”, “Current Ratio (CR)”, and “Quick’Ratio (QR)” on “Return On Asset (ROA)”. One of the pharmaceutical manufacturing companies, namely PT Pyridam Farma Tbk, is the company used in this study. Purpose Sampling is used to collect samples to be used. This study used descriptive and verification techniques, quantitative secondary data, and documentation techniques which were accessed through the company's official website respectively. This study uses descriptive analysis, classical assumption test, regression analysis, analysis of the coefficient of determination, and hypothesis testing (t-test and F-test) to answer the problem formulation. Based on the findings of partial hypothesis testing (t-test), the CR and QR affect ROA, while the DER and TATO do not. If the CR, QR, DER and TATO affect ROA of 82.7% and the remaining 17.3% is influenced by factors other or external factors, the results of simultaneous hypothesis testing (Test F) can be concluded.